The role of evolving concepts and new technologies and approaches in advancing pain research, management, and education since the establishment of the International Association for the Study of Pain : IASP 50th anniversary supplement - Flor, Herta; Noguchi, Koichi; Treede, Rolf-Detlef; Turk, Dennis C. (Pain, 2023)
The decades since the inauguration of the International Association for the Study of Pain have witnessed major advances in scientific concepts (such as the biopsychosocial model and chronic primary pain as a disease in its own right) and in new technologies and approaches (from molecular biology to brain imaging) that have inspired innovations in pain research. These have guided progress in pain management and education about pain for healthcare professionals, the general public, and administrative agencies.